Transient cortex blindness and global amnesia after performing left arm arteriography using iopamidol - Hueda-Zavaleta, Miguel (2020)
Iodinated contrast substances may cause different adverse events, most frequently renal involvement and hypersensitivity reactions. Transient cortical blindness and global amnesia are rarely described neurological complications after the administration of contrast substances. We report the case of a 63-year old patient with high blood pressure who presented with cyanosis and cold sensation affecting the second and third digits of his left hand. The patient underwent an arteriography of the left arm, where 50-mL of iopamidol was used as a contrast substance, and he immediately developed occipital headache associated to bilateral blurred vision that rapidly progressed to blindness. A cerebral computed tomography (CT) scan showed occipital subarachnoid hypodense areas, with no mass effect. Eighteen hours after the event, the patient showed retrograde amnesia with persistent amaurosis. His control cerebral CT scan did now show any focal disorder. The patient had a good progression, both bilateral amaurosis and headache subsided thirty hours after the event, and the patient was uneventfully discharged after ten days.